Becoming industrious female citizens: Work, discipline, and negotiation in Chinese female prison. (December 2020) - Hu, Yiqian; Liu, Liu
Abstract: Recent studies of incarcerated women have shifted from the "coping and adapting model" to the one that emphasizes the social analysis of penality, a punitive process that is recognized to be deeply intertwined with the outside society. This study adopted semi-structured interviews with 52 female prisoners and 13 female correctional officers in one Chinese prison. By conceptualizing prison work as a flexible institution, this study revealed that multiple meanings were given to prison work through various interactions between prisoners, between prisoners and correctional officers, and between prisoners and their family members. In addition, this study further highlighted that the disciplinary process of prison work was structured by both the prison environment and outside society. Based on the findings, a prisoner-oriented program is suggested as it could help Chinese female prisoners better reform and, most importantly, gain a sense of independence, respect, and dignity in their prison lives.